Chemical characterization and flexural strength of a denture base acrylic resin with monomer 2-tert-butylaminoethyl methacrylate - Rodriguez, Larissa Santana [UNESP]; Paleari, André Gustavo [UNESP]; Giro, Gabriela [UNESP]; de Oliveira Junior, Norberto Martins [UNESP]; Pero, Ana Carolina [UNESP] [UNESP]; Compagnoni, Marco Antonio [UNESP] (Wiley, 2013)
Purpose: The objectives of this study were to investigate the flexural strength (FS) and chemical interaction between 2-tert-butylaminoethyl methacrylate (TBAEMA) and a denture base acrylic resin. Materials and Methods: Specimens were divided into five groups according to the concentration of TBAEMA incorporated in acrylic resin Onda-Cryl (0%, 1%, 2%, 3%, 4%) and were submitted to Fourier transform infrared spectroscopy (FTIR), electron spectroscopy for chemical analysis (XPS-ESCA), and differential scanning calorimetry (DSC) analyses. FS of the specimens was tested, and results were analyzed by ANOVA/Tukey's test (α < 0.05). Results: Different nitrogen ratios were observed on specimens' surfaces: 0.36%, 0.54%, 0.35%, and 0.20% for groups 1%, 2%, 3%, and 4%, respectively. FTIR indicated copolymerization of acrylic resin and TBAEMA, and DSC results demonstrated a decrease in glass transition temperature (Tg). Significant differences were found for FS (p < 0.05). The mean values were 91.1 ± 5.5,A 77.0 ± 13.1,B 67.2 ± 12.5,B 64.4 ± 13.0,B and 67.2 ± 5.9B MPa for groups 0%, 1%, 2%, 3% and 4%, respectively (same superscript letters indicate no significant difference). Conclusions: The incorporation of TBAEMA in acrylic resin resulted in copolymerization and the presence of amine groups on specimens' surfaces, and in decreases of Tg and FS. © 2012 by the American College of Prosthodontists.
Keywords: Antimicrobial agents; Chemical properties; Poly(methyl methacrylate) resins; Strength